Resistance in health and healthcare: Applying Essex conceptualisation to a multiphased study on the experiences of Australian nurses and midwives who provide abortion care to people victimised by gender‐based violence. (18th October 2022) - Mainey, Lydia; O'Mullan, Cathy; Reid‐Searl, Kerry
Abstract: In this article, we explore the act of resistance by nurses and midwives at the nexus of abortion care and gender‐based violence. We commence with a brief overview of a multiphased extended grounded theory doctoral project that analysed the individual, situational and socio‐political experiences of Australian nurses and midwives who provide abortion care to people victimised by gender‐based violence. We then turn to Essex's conceptualisation of resistance in health and healthcare and draw upon these concepts to tell a unifying and cohesive story about how nurses and midwives exercise their politics. Vignettes taken from the three study phases are provided for demonstrative purposes. Finally, we discuss the potential of resistance in health and healthcare as a postmodern feminist research tool to analyse acts by nurses and midwives that could be categorised as political.